2013
DOI: 10.1039/c2ay25662b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-fouling surface coatings for applications in bacteremia diagnostics

Abstract: To accurately diagnose microbial infections in blood, it is essential to recover as many microorganisms from a sample as possible. Unfortunately, recovering such microorganisms depends significantly on their adhesion to the surfaces of diagnostic devices. Consequently, we sought to minimize the adhesion of methicillin-sensitive Staphylococcus aureus (MSSA) to the surface of polypropylene- and acrylic-based bacteria concentration devices. These devices were treated with 11 different coatings having various char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Prior to experiments, all device components were sterilized with 10% bleach and rinsed with sterile water. The molded funnels were then submerged in a beaker of 0.05% (w/v) Pluronic F-127 (Sigma-Aldrich) to minimize microbial adherence during the procedure. , The filled beaker was placed in a sonic bath for 10 min to facilitate adsorption of the Pluronic onto the parts’ surfaces.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Prior to experiments, all device components were sterilized with 10% bleach and rinsed with sterile water. The molded funnels were then submerged in a beaker of 0.05% (w/v) Pluronic F-127 (Sigma-Aldrich) to minimize microbial adherence during the procedure. , The filled beaker was placed in a sonic bath for 10 min to facilitate adsorption of the Pluronic onto the parts’ surfaces.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The brush conformation of PEO yields non-adhesive properties due to its highly hydrated polymer chains. Previous experiments have shown that Pluronic F-127 treatment reduces bacterial adhesion to plastic surfaces [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior to experiments, all device components were sterilized with 10% bleach and rinsed with sterile water. The molded funnels were then submerged in a beaker of 0.05% (w/v) Pluronic F-127 (Sigma Aldrich) to minimize microbial adherence during the procedure [ 37 ]. This beaker was placed in a sonic bath for 10 min to help facilitate adsorption of the Pluronic onto the parts’ surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…A recurring problem is the significant fraction of bacteria that is accidentally lost by non-specific binding in miniaturized devices and microfluidics due to their high surface area to volume ratios. Thus, antifouling properties are of greater importance [ 155 ]. Furthermore, fouling by non-specific biomolecules can also hinder sensitivity and selectivity and result in false-positive or -negative readings [ 156 ].…”
Section: Clinical–diagnostic Application Of Pathogen Adhesion Testsmentioning
confidence: 99%